Suppression of Δ(5)-androstenediol-induced androgen receptor transactivation by selective steroids in human prostate cancer cells - Chang, Hong-Chiang (The National Academy of Sciences, 1999)
Our earlier report suggested that androst-5-ene-3β,7β-diol (Δ(5)-androstenediol or Adiol) is a natural hormone with androgenic activity and that two potent antiandrogens, hydroxyflutamide (Eulexin) and bicalutamide (Casodex), fail to block completely the Adiol-induced androgen receptor (AR) transactivation in prostate cancer cells. Here, we report the development of a reporter assay to screen several selective steroids with anti-Adiol activity. Among 22 derivatives/metabolites of dehydroepiandrosterone, we found 4 steroids [no. 4, 1,3,5(10)-estratriene-17α-ethynyl-3,17β-diol; no. 6, 17α-ethynyl-androstene-diol; no. 8, 3β,17β-dihydroxy-androst-5-ene-16-one; and no. 10, 3β-methylcarbonate-androst-5-ene-7,17-dione] that have no androgenic activity and could also block the Adiol-induced AR transactivation in prostate cancer PC-3 cells. Interestingly, these compounds, in combination with hydroxyflutamide, further suppressed the Adiol-induced AR transactivation. Reporter assays further showed that these four anti-Adiol steroids have relatively lower glucocorticoid, progesterone, and estrogenic activity. Together, these data suggest some selective steroids might have anti-Adiol activity, which may have potential clinical application in the battle against the androgen-dependent prostate cancer growth.